he degree to which primary school teachers practice the principles of active education from the point of view of educational supervisors - dr.Hadeel Saleh Falih (Journal of College of Education, 2025)
The current research aims to: identify the degree to which primary school teachers practice the principles of active learning from the point of view of educational supervisors. To achieve this goal, the researcher built a questionnaire for this purpose consisting of (24) items The degree to which primary school teachers practice the principles of active learning is determined from the point of view of educational supervisors, and the criterion for answering it was according to a five-point Likert scale and is as follows: available in a degree (very little, little, moderate, great, very great), The results of the research showed that the degree of primary school teachers’ practice of the principles of active learning was with an arithmetic average of (3.96) and a high degree of availability, which is a good degree. The research recommended (providing an educational environment suitable for this type of learning and adding attached halls to schools in order to practice active learning strategies. Addressing decision-makers to provide financial rewards to teachers who obtain high standard percentages.